Biorenewable polymer composites from tall oil‐based polyamide and lignin‐cellulose fiber. Issue 48 (24th June 2015) - Liu, Kunwei; Madbouly, Samy A.; Schrader, James A.; Kessler, Michael R.; Grewell, David; Graves, William R.; Pantani, Prof. Roberto; Turng, Prof. Lih‐Sheng
ABSTRACT Tall oil‐based polyamide (PA) was blended with lignin‐cellulose fiber (LCF), an inexpensive, highly abundant byproduct of the pulp and paper industries, to produce environmental‐friendly thermoplastic biocomposites. The effects of the concentration of LCF on the thermal, rheological, and mechanical properties of the composites were studied using differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), thermogravimetric analysis (TGA), rheological testing, and mechanical testing. The morphologies of the composites were investigated using scanning electron microscopy (SEM). The incorporation of LCF did not change the glass relaxation process of the polyamide significantly. Results from rheological testing showed that the complex viscosity and shear storage modulus were increased by LCF. Both the modulus and strength increased with increasing LCF content; however, LCF substantially reduced the tensile elongation of the composites. The thermal stability of the composites was strongly influenced by the concentration of LCF. The onset of the degradation process shifted to lower temperatures with increasing LCF content. We conclude that LCF has strong potential for use as filler that is compatible with tall oil‐based polyamide. Adding LCF to form PA‐LCF composites can lower material costs, reduce material weight, and increase strength and rigidity compared to neat PA. Composites of PA‐LCF could serve as sustainable replacements for petroleum plastics in many industrial applications and would provide additional opportunities to utilize LCF, a highly abundant biorenewable material. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42592.